Fiber Optic Sensing Principle, Measurement and Applications - Liaw, Shien-Kuei (IntechOpen, 2019)
The chapters in this edited volume are by scholars/experts working in academia in Taiwan, Egypt, Israel, Germany and Japan. The contents are intended to provide a common forum for researchers, scientists and engineers throughout the world to exchange ideas and gain knowledge in the areas of fiber sensing technologies. The scope of the book includes the following chapters: 1. Introductory Chapter: An Overview of the Methodologies and Applications of Fiber Optic Sensing; 2. Theoretic Study of Cascaded Fiber Bragg Grating; 3. Femtosecond Transient Bragg Gratings; 4. Vital Sign Measurement Using FBG Sensor for New Wearable Sensor; 5. The State-of-the-Art of Brillouin Distributed Fiber Sensing. After a rigorous review process, the editors selected five submitted manuscripts (Chapters 2 to 5) for inclusion here. Three of these focus on the subject of point-to-point sensing using FBGs, and the final concerns distributed fiber sensing based on Brillouin scattering effect.